Improved Outlook Cropping Index Rice Field In Indonesia (Case : Central Sulawesi Province) - Darwis, Valeriana (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
Rice is the staple food of Indonesia’s main supply comes from the island of Java. During its development, the supply of Java progressively reduced, so as to meet the needs of the national rice production required the addition of outside Java. The addition of rice production in the short term can be done through an increase in the IP and through increased availability of water. One province outside Java which has a chance of it was Central Sulawesi province. This is due to: (i) this province there Gumbasa Irrigation Area, (ii) the use of the water is not effective, efficient and relatively more waste into the sea, (iii), the potential has not been optimized utilization of land and (iv) the productivity gap. Other requirements are considered to increase rice IP is: (a) sufficiently broad expanse of land, (b) the land in one unit of irrigation networks, (c) coordination with PU irrigation, (d) the mechanization of agriculture, and (e) plant cultivation technology and the use of short-lived seeds.